Does initial buccal crest thickness affect final buccal crest thickness after flapless immediate implant placement and provisionalization: A prospective cone beam computed tomogram cohort study. (3rd January 2022) - Staas, Tristan Ariaan; Groenendijk, Edith; Bronkhorst, Ewald; Verhamme, Luc; Raghoebar, Gerry Max; Meijer, Gerrit Jacobus
Abstract: Background: Flapless immediate implant placement and provisionalization (FIIPP) in the aesthetic zone is still controversial. Especially, an initial buccal crest thickness (BCT) of ≤1 mm is thought to be disruptive for the final buccal crest stability jeopardizing the aesthetic outcome. Purpose: To radiographically assess the BCT and buccal crest height (BCH) after 1 year and to calculate the correlation between initial and final achieved BCT. Materials and Methods: The study was designed as a prospective study on FIIPP. Only patients were included in whom one maxillary incisor was considered as lost. In six centers, 100 consecutive patients received FIIPP. Implants were placed in a maximal palatal position of the socket, thereby creating a buccal space of at least 2 mm, which was subsequently filled with a bovine bone substitute. Files of preoperative (T0), peroperative (T1) and 1‐year postoperative (T3) cone beam computed tomogram (CBCT) scans were imported into the Maxillim™ software to analyze the changes in BCT‐BCH over time. Results: Preoperatively, 85% of the cases showed a BCT ≤1 mm, in 25% of the patients also a small buccal defect (≤5 mm) was present. Mean BCT at the level of the implant‐shoulder increased from 0.6 mm at baseline to 3.3 mm immediate postoperatively and compacted to 2.4 mm after 1 year. Mean BCH improved from 0.7 to 3.1 mm peroperatively, and resorbed to 1.7 mm after 1 year. The Pearson correlation of 0.38 between initial and final BCT was significant ( p  = 0.01) and therefore is valued as moderate. If only patients (75%) with an intact alveolus were included in the analysis, still a "moderate correlation" of 0.32 ( p  = 0.01) was calculated. Conclusions: A "moderate correlation" was shown for the hypothesis that "thinner preoperative BCT's deliver thinner BCT's" 1 year after performing FIIPP.